2006
DOI: 10.1111/j.1467-9345.2006.00421.x
|View full text |Cite
|
Sign up to set email alerts
|

Dissonance between the digitally created words of school and home

Abstract: This article considers the potential for dissonance that one 12‐year‐old child (Clare) may experience as a text producer using new technologies, when working across a range of contexts. In this ongoing case study, two types of text are explored: a computer‐generated text produced as a homework task for school, and texts produced using an Internet‐based social network site called ‘Bebo’. Key features of Clare's text production in both contexts are identified and compared in an attempt to establish the dissonanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 11 publications
0
32
0
Order By: Relevance
“…It's really interesting! (Comment wall) Most research on writing in SNSs shows that it tends to strike a familiar register as users incorporate slang, disregard spelling and grammar rules, and create pithy texts (Dowdall, 2006;Greenhow & Robelia, 2009;Rowsell, 2009). Jenny's wordy and lengthy comments may have overwhelmed other users or put them off by the academic tone she adopted.…”
Section: Digital Literacies Snss and Discourse Communitiesmentioning
confidence: 97%
See 1 more Smart Citation
“…It's really interesting! (Comment wall) Most research on writing in SNSs shows that it tends to strike a familiar register as users incorporate slang, disregard spelling and grammar rules, and create pithy texts (Dowdall, 2006;Greenhow & Robelia, 2009;Rowsell, 2009). Jenny's wordy and lengthy comments may have overwhelmed other users or put them off by the academic tone she adopted.…”
Section: Digital Literacies Snss and Discourse Communitiesmentioning
confidence: 97%
“…To date, only a few studies have examined the literacy practices used in SNSs (see Davis, 2012;Dowdall, 2009;Greenhow & Robelia, 2009;Kirkland, 2008;Perkel, 2008;Rowsell, 2009) and even fewer have examined the use of SNSs in school settings (Dowdall, 2006;Moayeri, 2010). Further, although several studies focused on college students' use of Facebook, these studies did not examine their implications for academic learning (e.g., Deng & Tavares, 2013;Judd, 2013;Tsovaltzi, Puhl, Judele, & Weinberger, 2014).…”
Section: Digital Literacies and Snssmentioning
confidence: 98%
“…Moreover, whilst explored separately below, it is not suggested that these dimensions are experienced discretely. Studies have explored the interconnectedness between online and offline spaces in people's lives (Davies, 2006;Dowdall, 2006), and cautioned against conceptualising networked environments in ways that separate them from other environments (Leander, 2008). Instead, the intention is to explore how interactions between activity in material, connected and textual dimensions may be significant.…”
Section: The (Im)materiality Of Educational Spacementioning
confidence: 99%
“…Much recent work in this field has focused on practices in digital environments (e.g. see Davies, 2006;Dowdall, 2006), and there has been growing interest in connections and resonances between practices in different domains (Leander & Sheehy, 2004). Pahl & Rowsell, for example, have traced 'the flows of meanings across sites' (Pahl & Rowsell, 2006, p. 2), exploring how artefacts and practices traverse and are recontextualised in different sites and are inflected by local and global influences.…”
Section: Investigating Interactions Between Material Connected and Tmentioning
confidence: 99%
“…This is generally understood to mean that our textual practices find their motivation and occur across and within a range of communities – family, school, gang, Internet chat room, shopping mall, workplace – and a range of literature interrogates the practices of literacy in each of these, and other places. We can, for example, refer to Marsh (2006, 2007), Davies (2007), Alvermann (1999, 2002), Street (2003) and Dowdall (2006) for explorations of the out‐of‐school literacies of young children and adolescents. We can draw upon Gregory (2004), Auerbach (1989, 1995) and Purcell‐Gates (2004) in relation to family‐based literacy practices and diversity, while Scheeres (2002), Scheeres and Rhodes (2006), Wickert (2004) and Gee, Hull and Lankshear (1996) among others have interrogated the practices of literacy in workplaces and in relation to changing labour markets and adult literacy.…”
mentioning
confidence: 99%